INDEPENDENT WOMEN FARMERS BETWEEN MINORITIES AND THE POWER OF WOMEN BY FARMER WOMEN GROUP - M. Ali Sofyan; Ahmad Kharis (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
AbstractThe relationship between men and women is dominated by men. Likewise in village society, in all spaces women become the second class. This paper describes group activities to resist the concept that has been perpetuated as a concrete manifestation of the ideology of feminism. This activity is carried out by the Women Farmers Group (KWT Karya Tani), which is located in Pengalusan Village, Mrebet District, Purbalingga Regency, Central Java. The study approach uses qualitative (ethnography) because it is more to do a more comprehensive study. KWT Karya Tani's agricultural products are several types of organic vegetables. Some of them are processed into sambal kucai, gethuk and peuyeum. From the results of group production and management, KWT won 1st place at the national level from the Ministry of Agriculture, which previously won 1st place in Purbalingga Regency in the yard competition. As subordinated subjects, women in this group can create a solid integration. In addition, they are located in Christian groups, while most of the village society are Muslim. There is a stigma that tends to show social boundaries on the basis of religion. This can further strengthen solidarity and social integration. Finally, at this point, KWT Karya Tani has resisted and deconstructed the power of patriarchy and majority.